Ultrasound-Guided Percutaneous Nerve Stimulation in Post-Stroke Spasticity: A Case Report - Francesco Sartori; Albert Puig-Diví; Javier Picañol (Neurology International)
Introduction: Post-stroke spasticity (PSS) significantly impacts the quality of life for stroke survivors. While various treatments exist, options for refractory cases are limited. Ultrasound-guided percutaneous peripheral nerve stimulation (pPNS), commonly used in pain management, has not been studied for its potential use in spasticity management. This case report aims to evaluate the sensorimotor effects of pPNS in a patient with severe PSS. Case description: A 38-year-old male with severe PSS and functional limitations post-ischemic stroke in the middle cerebral artery underwent a six-week pPNS protocol (12 sessions). Low-frequency (2 Hz) stimulation targeted the median, musculocutaneous, and anterior interosseous nerves, while medium-frequency (10 Hz) stimulation targeted the posterior interosseous and radial nerves. Spasticity was assessed using the Modified Ashworth Scale (MAS) and Tardieu Scale (TS). Somatosensory assessments included tactile thresholds, pressure pain thresholds, and conditioned pain modulation (CPM). Outcomes: Spasticity decreased significantly, with reductions of 60.4% and 67.0% in elbow and wrist MAS scores, respectively, and a 49.5% reduction in TS scores. However, spasticity levels returned to baseline between sessions. Somatosensory assessments revealed increased tactile thresholds, decreased pressure pain thresholds, and an 81.3% reduction in CPM. The intervention was well tolerated, with minor transient effects, and the patient preferred pPNS over botulinum toxin injections. Conclusions: pPNS may effectively reduce spasticity and modulate somatosensory thresholds in PSS. These preliminary findings highlight its potential as an alternative treatment for refractory PSS, warranting further research with larger sample sizes and control groups to assess its broader clinical applicability.